2018
DOI: 10.3928/24748307-20181101-01
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Inadequate Health Literacy in a Population with Musculoskeletal Pain

Abstract: Musculoskeletal conditions are a major cause of ill health and disability. Inadequate health literacy may partly explain why musculoskeletal self-management programs are not effective for some patients. This study prospectively evaluated the impact of patients' health literacy level on their musculoskeletal pain and physical function (PF) following usual primary care. Primary care patients ( N = 4,720) who had consulted for musculoskeletal pain were mailed a baseline questionnaire; respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 22 publications
3
24
0
Order By: Relevance
“…In this current cohort just over 16% of the population were defined as low HL using the categorisations “always, often, sometimes” from the SILS measure following previous methodology [13, 24]. This percentage of low HL is similar to Morris et al [13] (who used the S-TOFHLA and report 17%) within their primary care population who were participating in a diabetes RCT.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In this current cohort just over 16% of the population were defined as low HL using the categorisations “always, often, sometimes” from the SILS measure following previous methodology [13, 24]. This percentage of low HL is similar to Morris et al [13] (who used the S-TOFHLA and report 17%) within their primary care population who were participating in a diabetes RCT.…”
Section: Discussionmentioning
confidence: 87%
“…This dataset was chosen for this study because consultations for musculoskeletal pain conditions are common in primary care (up to 20% of the primary care population will consult about musculoskeletal conditions in a given year [20]), and most often require significant patient/healthcare engagement and self-management over time, therefore potentially placing HL as an important factor for this patient population [2123]. Furthermore, a recent prospective study, using the KAPS dataset, showed those with low health literacy reported lower levels of physical function and higher levels of pain intensity at 6 months compared to those with adequate levels of health literacy, illustrating the relevance of HL status in this population [24].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed account of the history of epidemic and pandemic can be found in [1]. Throughout the history, it has been observed that inadequate knowledge about the disease, misinformation and misconception among populous, and improper handling of the situation caused more damage than it would have [2,3,4,5,6,7,8,9]. No wonder, in the case of Covid-19, we have acknowledged various confusing or sometimes conflicting information about the epidemic that affects the proper functioning of government.…”
Section: Introductionmentioning
confidence: 99%